Assessment of indoor radon, thoron concentrations, and their relationship with seasonal variation and geology of Udhampur district, Jammu & Kashmir, India. (3rd July 2017) - Kumar, Ajay; Sharma, Sumit; Mehra, Rohit; Narang, Saurabh; Mishra, Rosaline
Abstract: Background: The inhalation doses resulting from the exposure to radon, thoron, and their progeny are important quantities in estimating the radiation risk for epidemiological studies as the average global annual effective dose due to radon and its progeny is 1.3 mSv as compared to that of 2.4 mSv due to all other natural sources of ionizing radiation. Objectives: The annual inhalation dose has been assessed with an aim of investigating the health risk to the inhabitants of the studied region. Methods: Time integrated deposition based 222 Rn/ 220 Rn sensors have been used to measure concentrations in 146 dwellings of Udhampur district, Jammu and Kashmir. An active smart RnDuo monitor has also been used for comparison purposes. Results: The range of indoor radon/thoron concentrations is found to vary from 11 to 58 Bqm −3 with an average value of 29 ± 9 Bqm −3 and from 25 to 185 Bqm −3 with an average value of 83 ± 32 Bqm −3, respectively. About 10.7% dwellings have higher values than world average of 40 Bqm −3 prescribed by UNSCEAR. The relationship of indoor radon and thoron levels with different seasons, ventilation conditions, and different geological formations have been discussed. Conclusions: The observed values of concentrations and average annual effective dose due to radon, thoron, and its progeny in the study area have been found to be below the recommended level of ICRP. The observed concentrations of 222 Rn and 220 Rn measured with active and passive techniques are found to be in good agreement.